2008
DOI: 10.1002/jbm.b.31286
|View full text |Cite
|
Sign up to set email alerts
|

The influence of thermal treatment on the mechanical characteristics of a PLLA coiled stent

Abstract: We studied the effects of thermal treatment on the expansive characteristics of a coil-within-coil Poly(L-lactic acid) (PLLA) fiber stent developed at our institution to improve its mechanical performance and reproducibility. Following fabrication, furled stents were thermally treated at 62 degrees C for 25 min. The mechanical characteristics were measured compared with those of untreated stents when both were expanded via sequential balloon catheter pressure loading up to 12 atm. Treated stents reached full d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 53 publications
0
17
0
Order By: Relevance
“…[9][10][11] A promising approach to overcome the limitations of first generation DES is the application of fully bioabsorbable stents, which could be completely replaced by tissue, and may even allow for a positive vascular remodeling. 12 Apart from biodegradable polymers, such as polylactides, [13][14][15][16][17][18] stents based on the corrodible metals iron 19 and magnesium 20 have been proposed. So far, the magnesium stent is the only bioabsorbable metal stent investigated clinically as a coronary stent (PROGRESS-AMS trial).…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11] A promising approach to overcome the limitations of first generation DES is the application of fully bioabsorbable stents, which could be completely replaced by tissue, and may even allow for a positive vascular remodeling. 12 Apart from biodegradable polymers, such as polylactides, [13][14][15][16][17][18] stents based on the corrodible metals iron 19 and magnesium 20 have been proposed. So far, the magnesium stent is the only bioabsorbable metal stent investigated clinically as a coronary stent (PROGRESS-AMS trial).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, drug‐eluting stents (DES) loaded with anti‐proliferative drugs, such as sirolimus or paclitaxel, have been used extensively in percutaneous coronary interventions for the prevention of restenosis . Clinical application indicated that DES is successful in dealing with the acute vascular occlusion after PTCA and the postoperative restenosis of BMS . But DES has its own issues: these permanently existed metal implants in vessels will limit the normal movement of blood vessels and cause inflammatory reaction of vascular wall, which in turn will lead to a sequence of immunological and biochemical reactions as well as arterial wall hyperplasia and in‐stent restenosis.…”
Section: Introductionmentioning
confidence: 99%
“…PLLA was melt-extruded and drawn to a final diameter of 0.065 ± 0.01 mm [11]. The drawn fibers were then wound on a specially created jig to make the double opposed coiled stent.…”
Section: Methodsmentioning
confidence: 99%